Customer service: why it is so poor and how to improve it / Wan Kalthom Yahya - Yahya, Wan Kalthom (2003)
Everyone knows that customer service is important. By understanding that customers are their sole reason for the companies to be in the business and especially in today's highly competitive business environment, customer satisfaction makes a real difference. But, how many people and how many companies truly commit themselves in providing customers what they want and finding ways to improve the quality of their service? Companies need to be more people-conscious, because, customer service is everyone's job. If companies cannot care for the employees or colleagues welfare at work first, it is obvious companies will have hard time to get service out of the employees. Dissatisfied employees can never deliver good and quality service to other customers. The bottom-line is how the companies treat the employees.